2012
DOI: 10.1177/2151458512473827
|View full text |Cite
|
Sign up to set email alerts
|

Risk Factors for Acute Kidney Injury After Hip Fracture Surgery in the Elderly Individuals

Abstract: Objective: We aimed to evaluate possible risk factors assocıated wıth acute kidney injury (AKI) after hip fracture surgery in the elderly individuals. Design: Level II diagnostic study, evidence obtained from prospective cohort study from 1 center with level 2, and 3 patients. Patients: A total of 165 patients (>65 years) with femoral neck fracture were enrolled in this prospective study between 2007 and 2010. Two patients were dropped for inadequate laboratory follow-up data. Patients with kidney failure or r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

9
69
2

Year Published

2016
2016
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 65 publications
(84 citation statements)
references
References 33 publications
9
69
2
Order By: Relevance
“…(28,29). Our study similarly showed that a higher baseline creatinine level is an independent risk factor for AKI.…”
Section: Discussionsupporting
confidence: 71%
“…(28,29). Our study similarly showed that a higher baseline creatinine level is an independent risk factor for AKI.…”
Section: Discussionsupporting
confidence: 71%
“…Some authors suggest monitoring hourly urinary output in hip fracture patients. 4 However, AKI can exist even when urine output is normal. 7 On the other hand, oliguria can be an adaptive mechanism and is not systematically associated with AKI.…”
Section: Discussionmentioning
confidence: 99%
“…A c c e p t e d M a n u s c r i p t 4 The Doppler renal resistive index (RI) can be an effective means of early postoperative AKI diagnosis in scheduled major orthopaedic surgery. 8 However, to date, no predictive tool has been proposed in the case of hip fracture surgery.…”
Section: Page 4 Of 24mentioning
confidence: 99%
See 1 more Smart Citation
“…Postoperative complications may affect up to 20% of patients with hip fracture and the incidence of acute kidney injuries (AKI) among patients undergoing 9 9 arthroplasty for NOF# ranges between 16% to 24.4% in the literature (24,28).…”
Section: Discussionmentioning
confidence: 99%